Dimeglio Score Predicts Treatment Difficulty During Ponseti Casting for Isolated Clubfoot. Issue 5 (May 2019) - Brazell, Chris; Carry, Patrick M.; Jones, Alex; Baschal, Robin; Miller, Nancy; Holmes, Kaley S.; Georgopoulos, Gaia
Abstract : Background: The Dimeglio score (DS) is widely used to assess clubfoot severity, but its ability to predict long-term outcomes following Ponseti treated isolated clubfoot (IC) is controversial. This study tested the association between the initial DS and its individual parameters with the number of Ponseti clubfoot casts required to achieve correction and the rate of early recurrence following treatment. Methods: Data were retrospectively collected from patients who underwent treatment of IC between March 2012 and March 2015 and were followed for ≥2 years. DSs were collected at the initial casting visit. The number of Ponseti casts required to achieve clubfoot correction before tenotomy and recurrence of deformity were collected as the primary outcome variables. Recurrence was defined as any loss of correction leading to repeat casting or tenotomy during the bracing phase. Negative binomial and logistic regression analyses were used to test the association between the 8 Dimeglio parameters and number of casts and incidence of recurrence, respectively. Results: A total of 53 patients (37 male and 16 female) were included in the study. The median number of casts required to achieve an acceptable correction was 5 (range, 2 to 16). The incidence of recurrence was 24.53% (13/53). An increase in derotation, varus, equinus, muscle condition, and total DSs at the initial cast visit were associated with a significant ( P <0.05) increase in the number of casts required to achieve an acceptable correction. The derotation parameter [rate ratio: 1.30, 95% confidence interval (CI): 1.13-1.50, P =0.0003] was most strongly associated with number of casts. Total DSs at initial visit was the only variable significantly associated with the incidence of deformity recurrence (odds ratio: 1.36, 95% confidence interval: 1.01-1.84, P =0.0482). Conclusion: Initial DS is correlated with the number of casts required for correction in Ponseti treated IC. DS may help physicians establish realistic expectations for families with regard to the length of treatment and the possibility of recurrence following Ponseti treatment. Level of Evidence: Level II—retrospective prognostic study.